Strategi Implementasi Literasi Al-Qur’an Di Kalangan Guru PAI SMA Muhammadiyah 2 Surakarta - Ardha Zahro Nareswari; Hakimuddin Salim; Triono Ali Mustofa (Educatio, 2025)
This qualitative study examines the implementation of Qur'anic literacy at SMA Muhammadiyah 2 Surakarta. Key findings reveal: (1) The Al-Qosimi method, integrated with Qur'anic extracurricular activities and daily worship practices, creates a holistic learning ecosystem through tiered memorization assessments, differentiated classes (Tahfidz/Tilawah/Iqra), and Dhuha prayer/murojaah activities; (2) Teachers serve as facilitators, motivators, and role models using scaffolding approaches, repetition techniques, and creative methods; (3) Main supporting factors include student motivation, parental support, and adaptive methods, while challenges are addressed through integrated approaches and technology utilization. The program successfully enhances both Qur'anic literacy and the internalization of Islamic values. The study offers a practical model adaptable to other institutions, emphasizing the combination of active methods, teachers' multidimensional roles, and holistic approaches for sustainable Qur'anic literacy development.